Rapid literature review: definition and methodology - Beata Smela; Mondher Toumi; Karolina Świerk; Clement Francois; Małgorzata Biernikiewicz; Emilie Clay; Laurent Boyer (Journal of Market Access & Health Policy)
ABSTRACTIntroduction: A rapid literature review (RLR) is an alternative to systematic literature review (SLR) that can speed up the analysis of newly published data. The objective was to identify and summarize available information regarding different approaches to defining RLR and the methodology applied to the conduct of such reviews.Methods: The Medline and EMBASE databases, as well as the grey literature, were searched using the set of keywords and their combination related to the targeted and rapid review, as well as design, approach, and methodology. Of the 3,898 records retrieved, 12 articles were included.Results: Specific definition of RLRs has only been developed in 2021. In terms of methodology, the RLR should be completed within shorter timeframes using simplified procedures in comparison to SLRs, while maintaining a similar level of transparency and minimizing bias. Inherent components of the RLR process should be a clear research question, search protocol, simplified process of study selection, data extraction, and quality assurance.Conclusions: There is a lack of consensus on the formal definition of the RLR and the best approaches to perform it. The evidence-based supporting methods are evolving, and more work is needed to define the most robust approaches.